2018
DOI: 10.1002/adma.201804435
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Programmable Shape‐Morphing and Self‐Healing Organohydrogels Through Orthogonal Supramolecular Heteronetworks

Abstract: for applications in aerospace, smart devices, and biomedical materials. [1][2][3] Among these materials, shape-morphing polymers (SMPs) are particularly attractive because their forms can be programmed to perform transformations or motions in response to external stimuli (e.g., temperature, light, solvent, and electric fields). [3][4][5][6][7][8][9][10][11] Currently, two general approaches are used to obtain unparalleled shape-programming flexibility. The first involves geometric assistances to produce comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 30 publications
0
62
0
Order By: Relevance
“…Figure a illustrates the overview of biomimetic surface design inspired by the peristome surfaces of pitcher plants and the groove surfaces of rice leaves. Combining with programmable shape morphing effect of heteronetworks, we can realize multiple biomimetic structure topography on the organohydrogel surfaces. As we mentioned before, the shape memory performance of these organohydrogels is deeply involved in accomplishment of the biomimetic surface topography; to confirm this acclamation, we measured the thermoswitchable mechanics and the shape fixity ( R f )/recovery ( R r ) ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Figure a illustrates the overview of biomimetic surface design inspired by the peristome surfaces of pitcher plants and the groove surfaces of rice leaves. Combining with programmable shape morphing effect of heteronetworks, we can realize multiple biomimetic structure topography on the organohydrogel surfaces. As we mentioned before, the shape memory performance of these organohydrogels is deeply involved in accomplishment of the biomimetic surface topography; to confirm this acclamation, we measured the thermoswitchable mechanics and the shape fixity ( R f )/recovery ( R r ) ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a variety of flexible morphing systems have been developed with configurable soft materials by taking the advantage of various mechanisms such as asymmetric thermal expansion 5,6 , liquid crystalline transitions 7,8 , phase transitions [9][10][11][12] , and anisotropic swelling [13][14][15][16][17][18][19][20][21] , etc. To achieve shape programming and customization, numerous efforts have been made by applying specific chemical structures through a variety of polymeric materials including shape memory polymers (SMPs) [22][23][24][25] , vitrimer 26 , hydrogel [27][28][29] , organogel 30 . Application of two-way SMPs with a heterogeneous semi-crystalline structure or a broad melting transition realized reversible and controllable morphing behaviors [31][32][33] .…”
mentioning
confidence: 99%
“…Transformations between distinct configurations, which are not multistable, could be realized by multistep shape memorization complemented with an external force. [ 31,32 ] It has also been demonstrated that a kirigami‐based parylene film could conformally wrap the heart of a mouse, so that the sensing functions of the flexible electronics on it was enhanced. [ 33 ] These structures are usually realized passively by applying mechanical forces to form 3D configurations.…”
Section: Figurementioning
confidence: 99%